Combating the War on Terror in Kamila Shamsie’s Home Fire (2017) - Hasnul Insani Djohar; Iin Dwi Jayanti; Nada Tayem (UIN Syarif Hidayatullah Jakarta, 2024)
This paper investigates how Kamila Shamsie’s Home Fire (2017) resists the ideas of the War on Terror by using symbols, metaphors, and irony. This paper employs a qualitative method particularly close textual analysis. It engages with Bill Ascroft’s theory of postcolonialism to reveal the resistance of British Pakistanis to fight against the mantra of the War on Terror, which led to anti-Muslim racism in Britain. In doing so, Shamsie’s Home Fire undermines the ideology of the War on Terror by using literary devices mentioned previously and by representing how the three protagonists use essays and news to fight against neo-imperialist policies. Thus, Shamsie’s novel delves into the slogan of the War on Terror, using essays and news to challenge anti-Muslim racism in Great Britain, particularly in the aftermath of the 9/11 attack in the US. This novel reveals the connection between British colonialism and US imperialism in periods of global transnational capitalism rooted in white supremacy.